Role of Perceived Credibility towards Intention to Use of M-commerce - Salem M.A., Shamsudin M.F., Khairul Shahida Shabi, (Opción, 2019)
The article aims to investigate the role of perceived credibility towards an intention to use M-commerce via online survey questionnaire and regression analysis. As a result, all variables were related but when it is combined as a whole, it has been identified that only three independent variables from nine independent variables become as significant predictors to dependent variables which is an intention to use. In conclusion, established brand or company may have privilege in offering their products or services due to the confidence level among user.